Seasonality of meteorological drought parameters in Germany and their trends due to climate change - F. SKIERLO; J. J. GÓMEZ-HERNÁNDEZ; K. MIEGEL (Aerul şi Apa: Componente ale Mediului, 2018)
Climate change as a global problem affects the world on different scales, but its impact differs strongly between regions. Beside temperature, precipitation is another key element of the climatic system with at least the same importance. Regarding the precipitation regime, not only changes in the mean values have been detected, but also in the occurrence of extreme events and shifts in the seasonal distribution of precipitation throughout the year. With this background, our study investigates trends of meteorological drought in Germany as an example of what happens in a temperate climate zone. As indicators of dry spells we used the highest annual number of consecutive dry days, and the lowest precipitation within 40 days during one year as a new index. In addition, we analysed the annual and monthly total number of precipitation-free days as well as the total precipitation and its daily average on a monthly basis as further meteorological parameters. The results show an overall increase of the annual precipitation along with a decrease of the number of dry days per year. The highest annual number of consecutive dry days has also been decreasing, which means that dry spells are interrupted more often by significant precipitation and therefore are shorter. In accordance with the annual precipitation, the lowest precipitation during 40 consecutive days has also increased. As expected, the calculated linear trends of the parameters vary within the country and show a seasonal shift with stronger changes in certain month regarding the monthly precipitation, with a clear increase during the winter months. The results obtained using only precipitation-based meteorological parameters and our new index are in accordance with other results from the literature.